2022
DOI: 10.3390/pharmaceutics14081695
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid-Based Transferosomes for Topical Ocular Delivery of Cyclosporine A

Abstract: Delivering high-molecular-weight hydrophobic peptides, such as cyclosporine A, across the corneal epithelium remains a challenge that is complicated by other physio-anatomical ocular structures that limit the ocular bioavailability of such peptides. Transferosomes have previously been used to improve transdermal permeability, and have the potential for improving the ocular corneal permeability of applicable drugs. In this study, transferosomes for the potential ocular delivery of cyclosporine A were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Moreover, amorphization of the drug and perfect encapsulation within the lipid matrix of transferosomes resulted in the disappearance of the drug peak in the curcumin transferosome gel formulation Figure 7D . This observation is consistent with earlier studies that reported identical behaviors of drug-loaded vesicles in gel formulations 76 , 130 where the characteristic peaks of the tested drug products were vanished completely from the thermograms of drug loaded vesicles, indicating drug solubilization in the lipid phase and existence in amorphous state hence, the efficiency and success of the hydrophobic drug encapsulation within lipid matrix of the vesicles.
Figure 7 DSC thermogram of ( A ); Curcumin powder, ( B ) Freeze dried free curcumin gel, ( C ) Freeze dried plain gel, and ( D ) Freeze dried curcumin transferosomes gel.
…”
Section: Resultssupporting
confidence: 93%
“…Moreover, amorphization of the drug and perfect encapsulation within the lipid matrix of transferosomes resulted in the disappearance of the drug peak in the curcumin transferosome gel formulation Figure 7D . This observation is consistent with earlier studies that reported identical behaviors of drug-loaded vesicles in gel formulations 76 , 130 where the characteristic peaks of the tested drug products were vanished completely from the thermograms of drug loaded vesicles, indicating drug solubilization in the lipid phase and existence in amorphous state hence, the efficiency and success of the hydrophobic drug encapsulation within lipid matrix of the vesicles.
Figure 7 DSC thermogram of ( A ); Curcumin powder, ( B ) Freeze dried free curcumin gel, ( C ) Freeze dried plain gel, and ( D ) Freeze dried curcumin transferosomes gel.
…”
Section: Resultssupporting
confidence: 93%
“…Figure E depicts that bulk CsA exhibited a halo diffraction pattern, indicating an amorphous state consistent with the previous literature. , Nanosuspensions only showed diffraction peaks at 19.26 and 23.36°, which were also found in the pattern of TPGS, indicating that the amorphous form of CsA was maintained during the antisolvent precipitation and sonication processes. To further ascertain the physicochemical status of CsA, thermal behaviors of nanosuspensions were studied (Figure F), and it was found that the melting endotherm peak at 133 °C , and the decomposition peak at 228 °C of bulk CsA disappeared or shifted in the thermogram of NS, NS@lipid-PEG/CKC, and NS@lipid/CKC, which all showed an endothermic peak at 41 °C corresponding to the melting point of TPGS. This suggested the interaction between CsA and other ingredients. , …”
Section: Resultsmentioning
confidence: 99%
“…The research aimed to use transferosomes as potential CyA carriers in ocular delivery. For [122] The study examined the impact of surfactant Brij 98 on CyA release from p-HEMA lenses. The developed models predicted a correlation between an increase in surfactant content (fourfold increase) and a decrease in the percentage of CyA and Brij 98 release over time (twofold).…”
Section: Surfactantsmentioning
confidence: 99%